International experience of using report forms for hospital-based health technology asssessment - О. M. Filiniuk; М. М. Babenko (Фармацевтичний журнал, 2023)
Hospital-based health technology assessment (HB-HTA) is one of the components of public management and support hospital managers to science-based decision-making regarding the implementation of new and innovative health technologies (HT). HB-HTA includes the processes and methods used to make HTA reports in and for hospitals. Ukraine has already started implementing hospital-based HTA, but a number of steps are still needed to fully implement HTA at the hospitals. One of them is the choice of HB-HTA report form, which will be appropriate to use in the practical activities of hospitals in Ukraine.